Tensions in the American Dream rhetoric, reverie, or reality - Bush, Melanie E. L. 1955-; Bush, Roderick D. 1945-2013 (Temple Univ. Press., 2015)
"Could the promise of upward mobility have a dark side? In Tensions in the American Dream, Melanie and Roderick Bush ask, how does a "nation of immigrants" pledge inclusion, yet marginalize so many citizens based on race, class, and gender? The authors consider the origins and development of the U.S. nation and empire; the founding principles of belonging, nationalism, and exceptionalism; and their lived reality. Tensions in the American Dream also addresses the relevancy of nation to empire in the context of the historical world capitalist system. The authors ask, is the American Dream a reality only questioned by those unwilling or unable to achieve it? What is the "good life" and how is it particularly "American"?"..